2003
DOI: 10.1007/s00420-003-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene?an environmental and occupational toxicant

Abstract: For many years naphthalene had been considered as a non-carcinogenic polycyclic aromatic hydrocarbon (PAH). Airborne naphthalene concentrations have always been observed to be below the limit values of various national committees, such as the threshold limit value (TLV) of the American Conference of Governmental Industrial Hygienists (ACGIH) and the MAK of the Deutsche Forschungsgemeinschaft (DFG) (10 ppm). Since 2000, when the US National Toxicology Program revealed clear evidence of the carcinogenic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
2
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(183 citation statements)
references
References 186 publications
9
155
2
17
Order By: Relevance
“…Hara and Itani 13) summarized the median 1OHP as ranging between 0.03 and 0.27 µmol/mol Cr (0.06 and 0.53 µg/gCr) for nonsmokers and between 0.07 and 0.76 µmol/mol Cr (0.14 and 1.5 µg/gCr) for smokers. Mean 2NP ranging between 1.1 and 2.2 µg/l for non-smokers and between 5.1 and 17.2 µg/l for smokers has been reported 10) . In the results of our study, 1OHP was relatively lower, while 2NP was almost the same as those of previous studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hara and Itani 13) summarized the median 1OHP as ranging between 0.03 and 0.27 µmol/mol Cr (0.06 and 0.53 µg/gCr) for nonsmokers and between 0.07 and 0.76 µmol/mol Cr (0.14 and 1.5 µg/gCr) for smokers. Mean 2NP ranging between 1.1 and 2.2 µg/l for non-smokers and between 5.1 and 17.2 µg/l for smokers has been reported 10) . In the results of our study, 1OHP was relatively lower, while 2NP was almost the same as those of previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…The reasons for measuring them are that their urinary concentrations are relatively high and their measurements are easier compared to those of carcinogenic PAHs, such as benzo [a]pyrene. Recently naphthalene was reclassified as being possibly carcinogenic to humans by IARC in 2002 10) . Consequently, the importance of measuring naphthalene metabolite levels has increased.…”
mentioning
confidence: 99%
“…Naphthalene is one of polycyclic aromatic hydrocarbons (PAHs), which was commonly detected in China (Guo et al, 2012;Liu and Zhou, 2011;Ma et al, 2014), while seldom detected in the USA (Carter et al, 2008;Moran et al, 2004;Rowe et al, 2007). For many years, naphthalene had been considered as a non-carcinogenic PAH, but in 2000, the US National Toxicology Program revealed clear evidence of the carcinogenic activity of naphthalene in rats (Preuss et al, 2003). Hexachlorobutadiene is used as solvent, heat transfer liquid, as well as hydraulic liquid.…”
Section: Occurrence Assessmentmentioning
confidence: 99%
“…Results showed that OHI values of common VOCs (data are not shown) except naphthalene in the Yellow River basin and the Liaohe River basin were far below 1, so common VOCs rarely cause taste and odor problems. Naphthalene have not only been classified as a potential human carcinogen (Preuss et al, 2003), but also as an odor of mothballs (Young et al, 1996). Aldehydes were often reported to be associated with fishy odor episode (Suffet et al, 2004;Watson et al, 2001;Zhao et al, 2013).…”
Section: Olfactory Assessmentmentioning
confidence: 99%
“…As noted earlier, 1-Nap and 2-Nap are often used as prototype substrates for some SULTs in Phase-II drug metabolism research (Allali-Hassani et al, 2007;Arand et al, 1987). In the human body, urinary Nap has been pro-posed as a biomarker for the exposure to carbaryl (carbamate insecticide; 1-naphthyl methylcarbamate) applied in a variety of crops (Sams, 2017), and for workers occupationally exposed to naphthalene (Preuss et al, 2003(Preuss et al, , 2004Sams, 2017). Sulfate conjugation of xenobiotics by SULTs may alter the physico-chemical properties of those compounds that are bioactive, and is widely assumed to result in the inactivation of their biological activity (Mulder and Jakoby, 1990;Falany and Roth, 1993;Weinshilboum and Otterness, 1994).…”
Section: Structure Specificity Of Nap Derivatives On the Free Radicalmentioning
confidence: 99%